A possible mechanism to alter gyromagnetic factor - Jing-Ling Chen; Xing-Yan Fan; Xiang-Ru Xie (Results in Physics)
Dirac has predicted that the g factor of an electron is strictly equal to 2 in the framework of relativistic quantum mechanics. However, later physicists have found that this factor can slightly deviate from 2 (i.e., the problem of anomalous magnetic moments of leptons) when they consider quantum field theory. This fact thus renders the g factors of free leptons serving as precision tests for quantum electrodynamics, the standard model and beyond. In this work, we re-examine the problem of g factor within the framework of relativistic quantum mechanics. We propose a possible mechanism called the “electron-braidon mixing”, such that the g factor of an electron can be visibly altered. Our results shed new light to the problem of the anomalous magnetic moments of leptons.